Role and position of Indonesian Medical Disciplinary Honour Council: fair medical dispute resolution - Khalif Ardi, Muhammad; Laksito, FX Hastowo Broto; Laurent, Andriamalala (CV. Ius et Ambientis, 2023)
The main aim of this study is to offer a detailed account of the role and status of the Medical Ethics Council of Indonesia (MKDKI) in promoting the fair resolution of medical disputes in Indonesia. This study is a form of normative legal research. The research findings suggest that MKDKI should be the designated authority for resolving medical disputes since it has the requisite expertise in applying professional discipline in the medical domain. Moreover, MKDKI is a reputable organization assessing whether a physician has breached professional disciplinary norms. The phrase